Palladium surface modified La(0.6)Sr(0.4)Co(0.2)Fe(0.8)O(3-δ) hollow fibres for oxygen separation - Yacou, C.; Sunarso, J.; Lin, C.; Smart, S.; Liu, Shaomin; da Costa, J. (Elsevier B.V, 2011)
La(0.6)Sr(0.4)Co(0.2)Fe(0.8)O(3-δ) (LSCF) hollow fibres were prepared by a phase inversion/sintering method using polyetherimide as a binder. In order to overcome surface exchange kinetics limitation, LSCF hollow fibres were coated with ~200 nm palladium (Pd) nanoparticles. The O2 flux of best performing membranes increased by up to 350% in comparison to unmodified LSCF hollow fibres. Optimal enhancement was achieved with a single Pd coating. Additional coatings resulted in reduced O2 fluxes, thus counter acting the beneficial spill-over effect of the catalyst. Long term stability testing in atmospheric air at 850 °C showed that a LSCF membrane modified with a single Pd coating continually outperformed a pure LSCF hollow fibre for over 400 h, though the level of enhancement was reduced over time. A dramatic reduction in performance of more than 45% occurred within the first 24 h of testing, which was attributed to the coalescence and aggregation of Pd catalyst particles to ~1000 nm size at the LSCF grain boundaries. This greatly reduced the available area for the oxygen species to spill-over onto the LSCF surface and thus reduced the overall O2 flux.